Assessment of mental workload: A new electrophysiological method based on intra-block averaging of ERP amplitudes. (February 2016) - Horat, Sibylle K.; Herrmann, François R.; Favre, Grégoire; Terzis, Jorge; Debatisse, Damien; Merlo, Marco C.G.; Missonnier, Pascal
Abstract: The present study contributes to the current debate about electrophysiological measurements of mental workload. Specifically, the allocation of attentional resources during different complexity levels of tasks and its changes over time are of great interest. Therefore, we investigated mental workload using tasks varying in difficulty during an auditory oddball target paradigm. For data analysis, we applied a novel method to compute event-related potentials (ERPs) by intra-block epoch averaging of P2, P3a and P3b amplitude components for the infrequent target stimuli. We obtained eight consecutive blocks of 5 epochs each, which allowed us to develop an electrophysiological parameter to measure mental workload. In both the easy and the more constraining tasks, the amplitude of P2 decreased beginning with the second block of the sequence. In contrast, the amplitudes of P3a and P3b components linearly decreased following the repetition of the target in the more constraining task, but not in the easy task. Statistical analysis revealed intra-block differences on amplitudes of ERPs of interest between the easy and the more constraining tasks, confirming this method as a measure to assess mental workload. Since a subject is his own control, the present method represents an electrophysiological parameter for individual measurement of mental workload and may therefore be applicable in clinical routine. Highlights: First study to show attentional resource allocation disengagement post-first stimuli. Block-epochs averaging accounts for a reliable index of individual mental workload. Intra-block sweep averaging of P2 and P3a–P3b amplitude for workload measurement. Comparison of ERP blocks allowed elaborating individual measure of mental workload. P2 amplitude decreased from block 2; P3a and P3b amplitude from block 4 and block 3.